Sodna praksa v zvezi s trpinčenjem na delovnem mestu - Vukovič, Borut (Delavci in delodajalci, 2016)
The paper presents the case-law which has been formed in labour disputes on the prohibition of mobbing at workplace. Most disputes were about the exercise of employer's liability in the event of breach of this prohibition. From the perspective of individual elements of the tort cases, cases are presented in which the workers were awarded compensation for non-pecuniary damage. Also presented is a case of extraordinary termination of employment contract given to the worker on the grounds of breach of prohibition of workplace mobbing.
Keywords: delodajalci; delovni spor; delovno okolje; mobing; odškodnina; odškodninska odgovornost; pravna ureditev; preprečevanje; zaposleni